Penerapan Model Children’s Learning in Science Berbasis Kearifan Lokal pada Pembelajaran IPA Siswa Kelas IV SD Negeri 3 Srikaton - Tanti Meifisya; Asep Sukenda Egok; Armi Yuneti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to find out the results of science study of grade IV students of Srikaton State 3 Srikaton District Musi Rawas after the study model of Children's Learning in Science based on local wisdom. This research method uses experimental research methods with pre-test and post-test group experiment designs. Sampling is taken from the population, considering that there is only one class, the total sampling is 23 students. The instrument used is a question of description that amounts to 8 questions. Data collection is taken with test techniques. The data is analyzed using the